Methods of Overcoming Speech Disorders in Children (Study of the Experience of Prophet Moses in the Quran) - Rusiana, Rusiana; Harahap, Mardian Idris; Utami, Tri Niswati (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
The Qur'an gives instructions to everyone, including various goals. In Islam, al-Quran as a holy book that has medicinal powers (Shifa), especially in everyone who reads and listens to it with confidence. This paper aims to explore and analyze children who have difficulty speaking. Qualitative methods were used in subjects of several children aged 3 to 6 years, data were collected through interviews, observation and documentation of the author's intersubjectivity. Furthermore, interactive model techniques are carried out, namely data collection, data reduction, data presentation and conclusions. The findings explain that speech difficulties have actually been practiced since the time of Prophet Moses who asserted that when Prophet Moses asked Allah for prayers against him, this practice in the Qur'an illustrates that, in practice with methods and beliefs in the Quran has a good influence in overcoming speech difficulties in children.